Question #c9a3b

1 Answer

Answer:

See Below.

Explanation:

#2m^2 + 2m - 12 = 0#

#rArr 2m^2 + (6 - 4)m - 12 = 0# [First factorise the left hand expression]

#rArr 2m^2 + 6m - 4m - 12 = 0# [I choose 6 and 4 because #6 * 4 = 2 * 12#, and #6 - 4 = 2#]

#rArr 2m(m + 3) - 4(m + 3) = 0# [Group the like terms]

#rArr (m+3)(2m - 4) = 0# [Take the common part]

#rArr 2(m + 3)(m- 2) = 0#

#rArr (m+3)(m- 2) = 0#

If two numbers are multiplied and the answer is zero, then either of them must be zero or both of them.

So, Either, #m + 3 = 0#

#rArr m = -3#

Or, #m -2 = 0#

#rArr m = 2#

The solution of the quadratic equation is #m = -3, 2#